Psychometric Properties of the Patient Health Questionnaire-9 for Saudi Caregivers: A Cross-Sectional Study in Saudi Arabia - Salman M. Alreshidi PhD (SAGE Publishing, 2024)
To evaluate the psychometric properties of the Arabic-language Patient Health Questionnaire-9 (PHQ-9) among Saudi caregivers of patients with chronic diseases. Using a cross-sectional design, 94 Saudi caregivers (37 male and 57 female) in the medical city participated in the study. A comparative assessment was conducted on 4 models proposed in the existing PHQ-9 literature to gauge their compatibility through confirmatory factor analyses. This study evaluates convergent validity through a correlation analysis, examining the relationship between the PHQ-9 and the Depression, Anxiety, and Stress Scale-21 (DASS-21). Among the various models we examined, the single-factor structure of the PHQ-9 displayed the best fit with the data we gathered. Notably, the Cronbach alpha coefficient for the PHQ-9 registered at .81, indicating a high level of internal consistency. Factor loadings spanned a range from .39 to .76. The convergent validity of the PHQ-9 and DASS-21 was deemed satisfactory. It is established that the PHQ-9 serves as an effective tool for depression screening among Saudi caregivers in Saudi Arabia. Its strengths lie in its demonstrated validity, dependability, brevity, and convenience of administration, positioning it as a valuable resource for preventative measures and performance assessment within mental health settings.